Appearances and Disappearances in the images of artistic practice - Sanjuan, Ruth (Eikón / Imago, 2025)
We look at the images, but they also look at us. Images, as a texts, demand to be read and translated by the reader. They want to communicate things to us, stories. They want to reactivate themselves in every look and in every imagination. In images, as in texts, the information is not always evident, sometimes it is hidden, encrypted, wanting to be seen, decoded, rescued. Images in the context of artistic practice, especially those that will be addressed in this text, autobiographical images, speak of appearances and disappearances, a game that implies accepting that things -or bodies- can go from one place to another place, be and not be at the same time, like specters or ghosts that appear because they want to tell us something, because something was left untold and that's what they return to, that's why they appear. We can also understand that we have a vision when we look at them, when we are faced with the autobiographical images of these projects.